Molecular epidemiology of Candida albicans infections revealed dominant genotypes in waterfowls diagnosed with esophageal mycosis - Domán, Marianna; Makrai, László; Vásárhelyi, Balázs; Balka, Gyula; Bányai, Krisztián (Frontiers in Veterinary Science, 2023)
Fungal infections of animals could yield significant economic losses, especially in the poultry industry, due to their adverse effects on growth, feed intake, digestion, and reproduction. Previous investigations showed that Candida albicans plays the main etiological role in the esophageal mycosis of birds. In this study, we used multilocus sequence typing (MLST) to determine the population structure and molecular epidemiology of C. albicans isolated from geese and ducks in Hungary. Interestingly, only three known genotypes were identified among investigated flocks, namely, diploid sequence type (DST) 840, DST 656, and DST 605, suggesting the intra-species transmission of these genotypes. Additionally, two novel allele combinations (new DSTs) were found that have not been previously submitted to the MLST database. Phylogenetic analysis of isolates revealed a close relationship between DST 656 and DST 605 as well as between the two newly identified genotypes (designated DST 3670 and DST 3671). Although isolates from birds belonged to minor clades in contrast with most human isolates, no species-specificity was observed. Poultry-derived isolates were group founders or closely related to group founders of clonal complexes, suggesting that C. albicans is exposed to lesser selective pressure in animal hosts. The increasing number of genetic information in the C. albicans MLST database could help to reveal the epidemiological characteristics and evolutionary pathways that are essential for disease prevention strategies.